Plasma and Dietary Vitamin C Levels and risk of Gastric Cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST). - Jenab, M.; Riboli, E.; Ferrari, P.; Sabate, J.; Slimani, N.; Norat, T.; Friesen, M.; Tjønneland, A.; Olsen, A.; Overvad, K.; Boutron-Ruault, M.C.; Clavel-Chapelon, F.; et al. (Oxford University Press, 2006)
Vitamin C is an antioxidant and inhibitor of carcinogenic N-nitroso compound production in the stomach. Higher dietary vitamin C consumption is associated with decreased risk of gastric cancer (GC) in numerous case-control studies but data from prospective studies is limited, particularly so for blood measures of vitamin C. The objective of this study was to determine the association of plasma and dietary vitamin C levels with the risk of GC in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC), a large cohort involving 10 European countries. Using a fluorometric method, vitamin C was measured in pre-diagnostic plasma from 215 GC cases (matched controls=416). Conditional logistic regression models adjusted by body mass index, total energy intake, smoking status/duration/intensity and Helicobacter pylori (Hp) infection status were used to estimate relative cancer risks. No association with GC risk was observed for dietary vitamin C whereas an inverse GC risk was observed in the highest versus lowest quartile of plasma vitamin C (OR=0.55, 95%CI=0.31-0.97, Ptrend=0.043) which was maintained after exclusion of cases with ≤2yrs follow-up (OR=0.40, 95%CI=0.19- 0.83, Ptrend=0.064). The inverse association was more pronounced in subjects consuming higher levels of red and processed meats, a factor that may increase endogenous N-nitroso compound production. The effect of plasma vitamin C was not different by GC anatomical sub-site (cardia/non-cardia) or histological sub-type (diffuse/intestinal) and there was no significant interaction of effect with Hp. The results of this study show, in a prospective setting, an inverse association of GC risk with high levels of plasma vitamin C and suggest an interaction with the intake of red and processed meats, whose consumption may elevate endogenous Nnitroso compound production.
Keywords: Geneeskunde